A SYSTEMATIC REVIEW OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY FOR ELT - Ahmad, Siti Fauziah; Putri, Nazeera Fajriyanti; Tarihoran, Nafan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The role of Artificial Intelligence (AI) in learning and teaching English is becoming more significant in today's digital era. This study aims to analyze the use of AI in English Language Teaching (ELT) by identifying the most commonly used AI tools, their benefits, and challenges in implementation. Using a systematic review approach guided by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), this study systematically collected, selected and analyzed literature from academic databases such as Google Scholar, ScienceDirect, ERIC, DOAJ, and Mendeley. Articles were screened based on relevance, recency (published within the last five years), and accessibility (open access, English language). The results show that AI technologies such as chatbots, grammar correction tools, speech recognition systems, and machine translation platforms are widely used to improve students' pronunciation, listening comprehension, vocabulary acquisition, and writing skills. In addition, AI also facilitates personalized learning, reduces teacher workload, and promotes inclusive education. However, challenges such as limited accessibility, algorithmic bias, and ethical concerns must be addressed to ensure AI integration remains fair and effective in learning or teaching. This study provides valuable insights for educators and researchers in optimizing AI applications to improve the quality of English language learning or teaching while mitigating potential challenges. ABSTRAK Peran kecerdasan buatan dalam pembelajaran dan pengajaran bahasa Inggris menjadi semakin signifikan di era digital saat ini. Penelitian ini bertujuan untuk menganalisis penggunaan AI dalam Pengajaran Bahasa Inggris (ELT) dengan mengidentifikasi perangkat AI yang paling umum digunakan, manfaatnya, dan tantangan dalam implementasinya. Dengan menggunakan pendekatan tinjauan sistematis yang dipandu oleh PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), penelitian ini secara sistematis mengumpulkan, memilih, dan menganalisis literatur dari basis data akademis seperti Google Scholar, ScienceDirect, ERIC, DOAJ, dan Mendeley. Artikel disaring berdasarkan beberapa kriteria seperti relevansi, kemutakhiran (diterbitkan dalam lima tahun terakhir), dan aksesibilitas (akses terbuka, bahasa Inggris). Hasil penelitian menunjukkan bahwa teknologi AI seperti chatbots, alat koreksi tata bahasa, sistem pengenalan suara, dan platform penerjemahan mesin digunakan secara luas untuk meningkatkan pelafalan, pemahaman mendengarkan, akuisisi kosakata, dan keterampilan menulis siswa. Selain itu, AI juga memfasilitasi pembelajaran yang dipersonalisasi, mengurangi beban kerja guru, dan mempromosikan pendidikan inklusif. Namun, tantangan seperti aksesibilitas yang terbatas, bias algoritmik, dan masalah etika harus diatasi untuk memastikan integrasi AI tetap adil dan efektif dalam pembelajaran atau pengajaran. Studi ini memberikan wawasan yang berharga bagi para pendidik dan peneliti dalam mengoptimalkan aplikasi AI untuk meningkatkan kualitas pembelajaran atau pengajaran bahasa Inggris sekaligus mengurangi potensi tantangan yang ada.